Saintes/Mediolanum, cité des Santons et Bordeaux/Burdigala, cité des Bituriges Vivisques : destins croisés - Louis Maurin; Alain Bouet; Eneko Hiriart; Guilhem Landreau; Christophe Sireix; Dominique Tardy (Gallia)
Because of their “intertwined destinies” this single study unites Saintes/Mediolanum and Bordeaux/Burdigala to discuss how they passed under Roman domination. For a quarter-century archaeological and numismatic research has led us to believe that at the time of the outbreak of the Gallic War their histories were linked, something apparently confirmed by some interpretations of Caesar’s silences about the causes of his conflict with the Helvetii. Various indications have led to the belief that at that time the Santones had ambitions to exercise power over Bordeaux, considered the outlet of the Gallic isthmus, but these were as yet unstable. Recent archaeological research has shown that the two cities had very different origins. Bordeaux originated around 600 BC as a trading-post on the left bank of the Gironde; Mediolanum perhaps originated, and this before the Gallic War, in the movement to the left bank of the Charente of the oppidum of the Santones, until then doubtless situated at Pons. This people figures amongst the great losers from the Caesarian conquest; the extent of their territory was reduced in the south and –as seems to be very probable– the Romans created next to them a new power, that of the Bituriges Vivisci, uprooted from the Berry and transferred to the estuary; the little emporium of Bordeaux was their capital. Augustus constituted the Bituriges Vivisci a civitas, like the Santones, and their capitals were ornamented with sanctuaries of the imperial cult. Their political institutions were similar; inscriptions show that, whilst bearing the stamp of Gallic form, they perpetuated the power of the former ruling class, now allied to Rome.In the generation that followed the Gallic War both Mediolanum and Burdigala saw rapid development in similar aspects. Both cities flourished in the Augustan period and, so far as can be seen, their growth was in parallel in the first half of the 1st c. AD, above all in the establishing of an urban layout and the construction of structures for convenience and health (fountains, aqueducts); though none of this is that distinctive for Roman Gaul. The cultural imprint of the period of Independence was clearly more pronounced at Saintes, and from the last twenty years BC to the middle of the 1st c. AD this city benefited from a properly Roman suite of major architectural embellishments which gave it a glamour unrivalled by its neighbour or by the other civitates of the new province of Aquitania.